2009
DOI: 10.1093/intimm/dxp014
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 production by an established lymph node stromal cell line via lymphotoxin-beta receptor engagement involves the cooperation of multiple signaling pathways

Abstract: Non-hematopoietic mesenchymal stromal cells in secondary lymphoid organs play pivotal roles in tissue organization and immune responses by exhibiting specialized features such as the production of lymphoid homeostatic chemokines. However, the maturational process of stromal cells mediated by lymphotoxin-beta receptor (LTbetaR) signaling, a key for stromal maturation, remains unclear. Taking advantage of a stromal cell line established from mouse lymph node, which can produce a homeostatic chemokine, CXC chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…As another example, the Cxcl13 is a chemokine ligand in B cells with a C-X-C motif. It has already been established that Cxcl13 induction requires activation of canonical and non-canonical Nf-kB pathways (Suto, et al, 2009), which confirms the prediction of this gene in our network. These data strongly support the predictions generated by our analysis.…”
Section: Defining Bn+1 Genessupporting
confidence: 89%
“…As another example, the Cxcl13 is a chemokine ligand in B cells with a C-X-C motif. It has already been established that Cxcl13 induction requires activation of canonical and non-canonical Nf-kB pathways (Suto, et al, 2009), which confirms the prediction of this gene in our network. These data strongly support the predictions generated by our analysis.…”
Section: Defining Bn+1 Genessupporting
confidence: 89%
“…Contrasting with the negative regulation of CXCL12 expression in HUVEC, studies in lymph node stromal cells (12,14) and smooth muscle cells (13) showed that TNF stimulation enhanced LT␤R ligation-induced expression of CXCL13. We did not detect CXCL13 in HUVEC or dermal EC (11), suggesting that the expression profiles of NC NF-B-dependent genes are cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…TNF markedly up-regulates p100 levels in EC via classical NF-B signaling, although it does not activate the NC pathway or induce CXCL12 expression (11). Previous studies demonstrated that TNF enhances expression of the NC gene CXCL13 induced by anti-LT␤R in lymph node stromal cells and aortic smooth muscle cells (12)(13)(14). Furthermore, antigen receptor ligation on B cells has been shown to increase p100 levels providing a pool of p100 for BLyS-induced NC signaling (15).…”
Section: Activation Of Vascular Endothelial Cells (Ec)mentioning
confidence: 99%
“…Growth of developing CPs relies on the continued cross talk between LTi cells, which express RANK, RANKL and CXCR5, and VCAM-1 ϩ organizer cells that express RANKL and CXCL13 upon LT␤R signaling. 34,35 Decreased LT␣ 1 ␤ 2 expression caused by absence of RANKL may lead to loss of CXCL13 expression, which in turn inhibits further CP development and prevents their maturation into ILFs.…”
Section: Discussionmentioning
confidence: 99%